The DNA Methylation Inhibitor Zebularine Controls CD4+ T Cell Mediated Intraocular Inflammation - Zou, Yanli; Hu, Xiao; Schewitz-Bowers, Lauren P.; Stimpson, Madeleine; Miao, Li; Ge, Xiaofei; Yang, Liu; Li, Yan; Bible, Paul W.; Wen, Xiaofeng; Li, Jing Jing; Liu, Yizhi; et al. (Frontiers in Immunology, 2019)
CD4+ T cell mediated uveitis is conventionally treated with systemic immunosuppressive agents, including corticosteroids and biologics targeting key inflammatory cytokines. However, their long-term utility is limited due to various side effects. Here, we investigated whether DNA methylation inhibitor zebularine can target CD4+ T cells and control intraocular inflammation. Our results showed that zebularine restrained the expression of inflammatory cytokines IFN-γ and IL-17 in both human and murine CD4+ T cells in vitro. Importantly, it also significantly alleviated intraocular inflammation and retinal tissue damage in the murine experimental autoimmune uveitis (EAU) model in vivo, suggesting that the DNA methylation inhibitor zebularine is a candidate new therapeutic agent for uveitis.